« The inalienable right to existence »: Corinne Rocheleau-Rouleau, militante pour l'instruction des personnes sourdes et historienne des francophones d'Amérique - Lavoie, Pierre (Profession historienne? Femmes et pratique de l’histoire au Canada français, XIXe-XXe siècles, 2023)
Keywords: Femmes; Francophones; Histoire; Sourds

Black slavery, historians and textbooks: A study of the representation of enslaved people of African descent in Quebec's historiography and history textbooks - Roethlisberger, Susanne (Université McGill, 2020)
Keywords: Africains; Esclaves; Histoire

Roman familial, roman national? L'histoire de Montréal sous la loupe de la filiation généalogique féminine (Première partie) - Deslandres, Dominique (Les Cahiers des Dix, 2020)
Keywords: Autochtones; Famille; Femmes; Français; Mariage

Le boulevard Saint-Laurent et son histoire - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
Keywords: Routes; Saint-Laurent (rue)

Le boulevard Saint-Laurent et son histoire-(suite 1) - Tessier, Stéphane (Il était un fois... Montréal Nord, 2023)
Keywords: Juifs; Saint-Laurent (rue)

Le boulevard Saint-Laurent et son histoire-(suite 2) - Tessier, Stéphane (Il était un fois... Montréal Nord, 2023)
Keywords: Chinois; Juifs; Saint-Laurent (rue)

Histoire des communautés noires au Québec et à Montréal (1ère partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
Keywords: Esclaves; Noirs

Histoire des communautés noires au Québec et à Montréal (3e partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
Keywords: Haïtiens; Noirs

Histoire des communautés noires au Québec et à Montréal (2e partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
Keywords: Chemins de fer; Musique; Noirs; Travail

Il fallait se défendre: l'histoire du premier gang de rue haïtien à Montréal - Aurélien, Maxime; Rutland, Ted (Mémoire d'encrier, 2023)
Keywords: Criminalité; Délinquance; Haïtiens; Noirs

Montréal, haut lieu de la diplomatie autochtone - Arsenault, Mathieu (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Autochtones; Parlement

Les " jeunes ", les " amazones ", les " célestes ": les figures de la panique morale sur les drogues à Montréal dans le journal La Patrie, entre 1921 et 1923 - Grenier, Amélie (Bulletin d'histoire politique, 2020)
Keywords: Chinois; Criminalité; Femmes; Patrie (La); Réformistes

"Un programme unique dans le monde entier": le Congrès juif canadien et la lutte pour le droit à l'égalité "raciale" et religieuse au Québec (1945-1950) - Rainville, Paul-Etienne (Histoire sociale / Social History, 2020)
Keywords: Congrès juif canadien; Juifs

Henri Bourassa, les Franco-Américains et la Première Guerre mondiale - Lamarre, Jean; Dubé, Alexandre (Bulletin d'histoire politique, 2021)
Keywords: Américains; Bourassa, Henri; Conscription; Francophones; Guerre

Éclairer et perfectionner l’esprit : l’éducation libérale et le délicat compromis entre raison et foi dans les écoles classiques de langue anglaise au Bas-Canada (1800-1840) - McCutcheon, Shawn (Études d'histoire religieuse, 2022)
Keywords: Langue; Libéralisme

« Le Québec connaîtrait-il l’agonie du Chili ? » : l’influence de « l’expérience chilienne » sur l’évolution du Parti québécois au tournant des années 1970 - Barry-Shaw, Nikolas (Bulletin d'histoire politique, 2023)
Keywords: Chiliens; Indépendantisme; Partis politiques

Du pragmatisme à l’engagement. Les militants chiliens à Montréal et leurs relations avec le milieu politique local : influences et interactions réciproques - Del Pozo, José (Bulletin d'histoire politique, 2023)
Keywords: Chiliens

À la défense du peuple chilien : la connexion religieuse québécoise avec la résistance chilienne durant la dictature d’Augusto Pinochet - Demers, Maurice (Bulletin d'histoire politique, 2023)
Keywords: Chiliens; Missions

Du Chili d’Allende au Québec : inspirations et parcours du Réseau des politisés chrétiens (1969‑1972) - Foisy, Catherine; Genois-Lefrançois, Christophe (Bulletin d'histoire politique, 2023)
Keywords: Chiliens

Les Québécois et la solidarité avec le Chili, 1970‑1990 - Hervas, Roberto (Bulletin d'histoire politique, 2023)
Keywords: Chiliens; Confédération des syndicats nationaux

La Maison d’Haïti: Haitian Stories of Resistance and Black Diasporic Activism in Montréal, 1972–1986 - Rochat, Désirée (Histoire sociale / Social History, 2022)
Keywords: Haïtiens; Noirs

« Glad of your help »: Scottish Architects in Montreal, 1860-1940 - Adams, Annmarie (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Golden Square Mile; Royal Victoria Hospital; Écossais

Le Montréal juif – (2e partie) - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2021)
Keywords: Juifs

Le Montréal juif – (4e partie et fin) - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2022)
Keywords: Juifs

Mainmise sur la contre-culture américaine: la traduction comme véhicule de transfert culturel - Ruschiensky, Carmen (Relire les revues québécoises: histoire, formes et pratiques (XXe-XXIe siècle), 2021)
Keywords: Traduction

“The Most Distinctively Canadian City” Representations of the City in Montreal Guidebooks, 1876–1892 - Lamoureux, François (Urban History Review/Revue d'histoire urbaine, 2023)
Keywords: Anglophones; Métropole; Tourisme

Sur les traces des immigrants qui se marient dans la vallée du Saint-Laurent pendant la première moitié du XVIIIe siècle - Rompillon-Tran, Samantha (Revue d'histoire de la Nouvelle-France, 2023)
Keywords: Français; Mariage

“The People Who Stayed”: Back River Memorial Gardens Cemetery as a Site of Jewish Migrant and Montreal Urban Meaning-Making - Frost, Naomi; Sheftel, Anna (Urban History Review / Revue d'histoire urbaine, 2024)
Keywords: Ahuntsic; Cimetières; Juifs

S'unir dans l'émotion: le Congrès international de 1929, moment charnière d'affirmation des gardes-malades canadiennes-françaises - Klein, Alexandre; Larose-Dutil, Hubert (Revue d'histoire de l'Amérique française, 2023)
Keywords: Femmes; Francophones; Infirmières

« Des mots et des commandements déplacés ». La prise en charge des étudiants vietnamiens du Plan Colombo à l’Université de Montréal (1950–1959) - Poitras, Daniel (Historical Studies in Education / Revue d'histoire de l'éducation, 2023)
Keywords: Université de Montréal; Vietnamiens; Étudiants

La paroisse Holy Family: une empreinte de la présence anglophone dans l'arrondissement - Vailles, Alexis (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2024)
Keywords: Anglophones; Rosemont; Églises

Les Seigneurs sulpiciens, les Autochtones et le Fort Lorette - Lapointe, Alexandre (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2020)
Keywords: Autochtones; Communautés religieuses; Fort de la montagne; Forts; Missions; Sault-au-Récollet; Sulpiciens

Un Iroquois et des Algonquins de Sault-au-Récollet témoignent au procès d’un contrebandier - Duff, Jocelyn (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2020)
Keywords: Alcool; Autochtones; Communautés religieuses; Criminalité; Iroquois; Jésuites; Magasins; Missions; Sault-au-Récollet; Sulpiciens

Les captifs anglais de la mission de la Nouvelle-Lorette - Lapointe, Alexandre (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2021)
Keywords: Autochtones; Communautés religieuses; Forts; Guerre; Iroquois; Missions; Sulpiciens

Du Centro Donne Italiane di Montréal aux Donne d’Acciaio. - Lebleu, Jacques (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2023)
Keywords: Ahuntsic; Femmes; Féminisme; Italiens

Les Irlandais catholiques de Montréal : genèse d'une communauté, 1800-1834 - Duchesne, Jonathan (Université du Québec à Montréal, 2021)
Keywords: Famille; Irlandais; Mariage

Elites and Scottishness in Montreal: identity, culture and the self in portait photography, 1860-1900 - Regimbald-Roy, Florence (Université McGill, 2021)
Keywords: Notman, William; Photographie; Écossais

'' Des Québécois comme les autres ''? Les communautés culturelles dans le projet politique et national du Parti québécois (1968-1981) - Rose, Jérémie (Université de Sherbrooke, 2020)
Keywords: Indépendantisme; Langue; Nationalisme; Partis politique

Parcours migratoires et re-constructions identitaires de femmes d'ascendance maghrébine à Montréal - Boukerrou, Yasmine (Université du Québec à Montréal, 2022)
Keywords: Femmes; Maghrébins

Redéfinir le Canada et le Québec : les représentations identitaires du Centenaire de la Confédération et de l'Expo 67 chez les journalistes - Blais, Caroline (Université du Québec à Montréal, 2021)
Keywords: Anglophones; Expositions; Francophones; Journalistes

Montréalaises d'origine haïtienne : communauté d'entraide et luttes féministes de 1970 à 1995 - Bélanger, Jasmine (Université du Québec à Montréal, 2020)
Keywords: Femmes; Féminisme; Haïtiens

Le Québec anglophone: une communauté distincte du reste du Canada? : étude comparative des positions éditoriales de deux journaux anglophones - The Gazette et The Globe and Mail - en rapport avec certains débats publics au Québec et au Canada de 1976 à 1982 - Lacasse, Chantal (Université Laval, 2022)
Keywords: Anglophones; Francophones; Fédéralisme; Indépendantisme; Montreal Gazette; Nationalisme

Remembering the Duvalier era: Resistance, Exile, and Solidarity in the Life Stories of Haitian-Montrealers - Riou, Geneviève (Université Concordia, 2022)
Keywords: Haïtiens

Idealized Spaces, Internationalized Selves: Japanese Migration to Montreal, Canada, 1990-Present - Tabakow, Elizabeth (Université Concordia, 2021)
Keywords: Japonais

Between Crisis and Preservation: The Canadian Jewish Congress and the Quebec Nationalist Movement, 1976-1980 - Mercado, Ryan (Université Concordia, 2020)
Keywords: Anglophones; Congrès juif canadien; Francophones; Indépendantisme; Juifs; Nationalisme

McGill University’s racial exclusion of Japanese Canadians, 1943-1945 - Elsworthy, Tess (Université McGill, 2020)
Keywords: Japonais; Université McGill

A Fractured Identity: The 1980 Referendum and the Italians of Montreal - Pannunzio, Anthony (Université McGill, 2022)
Keywords: Indépendantisme; Italiens; Nationalisme; Référendums

Una gatta da pelare : vies publiques et vies privées des Italiennes récemment arrivées à Montréal - Vigliano, Chiara (Université de Montréal, 2021)
Keywords: Femmes; Italiens

Montréal, Heart of Indigenous Diplomacy - Arsenault, Mathieu (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Autochtones; Parlement

Negotiating Bella Figura: Inside the Childhood Homes of Six Second-Generation Italian-Canadian Women in Montreal - Massa, Lisa (Université Concordia, 2022)
Keywords: Enfants; Femmes; Italiens

Tim Tim? Bwa Chèch! : Documentation de la présence des artistes visuels haïtiens à Montréal 1971-1986 - Theliar-Charles, Kessie (Université Concordia, 2023)
Keywords: Haïtiens

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (Études d'histoire du Québec / Studies on the History of Quebec, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."--
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail